2015
DOI: 10.1111/acer.12778
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Alcohol Consumption and Colorectal Cancer Risk

Abstract: The association between the amount of alcohol consumed and the incidence of CRC was not significant at moderate intake levels. Moderate alcohol consumption was associated with a reduced CRC risk in study populations with greater adherence to a Mediterranean diet, where wine contributed substantially to the alcoholic beverage consumed. Other factors such as obesity, folate deficiency, and genetic susceptibility may contribute additional CRC risk for those consuming alcohol. To minimize CRC risk, appropriate rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 34 publications
0
43
0
9
Order By: Relevance
“…20 Alcohol damages the epithelial cells of the intestinal tract through direct and indirect means, assisting the absorption of acetaldehyde, a recognized carcinogen, and facilitating the production of species that proliferate DNA damage, oxidative stress, and lipid peroxidation in the intestinal lumen. 20 Increased alcohol intake can also lead to a suppression of immune surveillance, which could impact both CRC risk and progression. 20 Our results indicated no association between overall pre-diagnostic alcohol consumption and survival, but also hinted at a potentially less favorable prognosis given higher daily liquor intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Alcohol damages the epithelial cells of the intestinal tract through direct and indirect means, assisting the absorption of acetaldehyde, a recognized carcinogen, and facilitating the production of species that proliferate DNA damage, oxidative stress, and lipid peroxidation in the intestinal lumen. 20 Increased alcohol intake can also lead to a suppression of immune surveillance, which could impact both CRC risk and progression. 20 Our results indicated no association between overall pre-diagnostic alcohol consumption and survival, but also hinted at a potentially less favorable prognosis given higher daily liquor intake.…”
Section: Discussionmentioning
confidence: 99%
“…20 Increased alcohol intake can also lead to a suppression of immune surveillance, which could impact both CRC risk and progression. 20 Our results indicated no association between overall pre-diagnostic alcohol consumption and survival, but also hinted at a potentially less favorable prognosis given higher daily liquor intake.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive dose-response meta-analysis also corroborated these findings, the RR for heavy drinkers compared with non-drinkers and occasional drinkers being 1.44 for CRC [30] . However, moderate alcohol consumption (<30 g/day) was not significantly associated with the incidence of CRC, and other factors, including a Mediterranean diet, folate deficiency and genetic susceptibility, would convert this association [31] . Nevertheless, another meta-analysis of light alcohol drinking (up to 1 drink/day) and cancer also showed no association for CRC, but an increasing risk of oral cavity, pharynx, esophagus and breast cancer [32] .…”
Section: Alcoholmentioning
confidence: 91%
“…Klarich et al previously reviewed 21 articles on the association between the degree of alcohol intake and CRC occurrence. They suggested that moderate alcohol consumption (<30 glum/day) was not associated with the incidence of CRC [32]. In the present study, we only analyzed the presence of alcohol consumption habits.…”
Section: Discussionmentioning
confidence: 89%